Investigation of the carbon monoxide post-combustion flame in the working space of a steelmaking unit - Yakovleva, Irina; Petrik, Aleksey (Eastern-European Journal of Enterprise Technologies, 2017)
In order to optimize thermal mode of the steelmaking process and to bring down energy consumption, we examined effect of thermophysical parameters of the carbon monoxide post-combustion flame considering aerodynamic processes on the thermal-technological parameters during melting. Based on modern approaches and methods, we obtained data on the character of macro-physical processes that occur in the working space of the unit and in the reaction zone, taking into consideration the influence of aerodynamic processes in the bath of a steelmaking unit. We conducted a comparative analysis of the shape and temperature fields of the flame taking into consideration the influence of aerodynamic processes at different intensities of blowing the bath of a steelmaking unit with oxygen for different types of blowing devices. It was established that the shape and magnitude of temperature fields of the drigted flame varies depending on the content of carbon (from 4 to 0.1 %) in the melt, the intensity of blowing the bath with oxygen (from 1,800 to 2,400 m3/h), as well as design features of the blowing device (nozzle diameter and inclination angle). In this case, lances with an increase in the inclination angle of the nozzles to 50° and varying nozzle diameters from 10 to 20 mm, compared to lances of basic design (at the same inclination angles), make it possible to improve flame organization, to increase the length and temperature of the flame, to improve uniformity of the structure of flame, to increase heat exchanging surface between the flame and the bath, and to improve heating capability of the bath in a steelmaking unit. The studies reported in the present paper are applicable to industrial steelmaking units with the intensity of blowing the bath with oxygen in a range of 1,800‒2,400 m3/h. The results obtained bring us closer to the development of a rational design of the blowing device to optimize the thermal mode of steelmaking process that will make it possible to reduce energy consumption in steel production.